POVERTY ALLEVIATION STRATEGY IN TIBAWA GORONTALO DISTRICT - Widiantoro, Mohamad Agung; Aneta, Asna; Aneta, Yanti (Public Policy Journal, 2020)
This research aims to: (1) analyze the poverty alleviation strategy in Tibawa Gorontalo District and (2) find the factors of the successful poverty alleviation strategy in Tibawa Gorontalo District. This research uses a descriptive-qualitative method with three data collection techniques i.e. (1) closed interview, (2) observation, and (3) documentation. Data were analyzed using Huberman and Miles’s plot comprising (1) data reduction, (2) data display, and (3) data verification and conclusion drawing. This research figures out that: 1) The implementation of the poverty alleviation strategy in Tibawa Gorontalo District is still considered poor due to: a) Planning, b) Implementation, and c) Evaluation and 2) Factors that determine a successful poverty alleviation strategy in Tibawa Gorontalo District are: a) the government supports, b) budget, c) the community supports, and d) the organization supports. Our recommendations are thus: 1. The poverty alleviation strategy in Tibawa Gorontalo District is still considered poor despite the village funds that have been allocated to the poverty alleviation besides the supports from the Social Service and 2. The determinants of a poverty alleviation strategy in Tibawa Gorontalo District are the community supports. Meanwhile, the amount of budget to poverty alleviation should be increased to encourage the poor community in business.